Tribocorrosion Behavior of Laser-Cladded FeCrBSi Medium-Entropy Alloy Coatings - WANG Yanfang, ZHANG Yunpeng, CAO Chenjie, LIU Yanle, WANG Yunxuan, SHI Zhiqiang (Cailiao Baohu)
Marine oil and gas engineering equipment suffers significant damage due to seawater corrosion and mechanical wear.Medium-entropy alloys， with their combined wear and corrosion resistance， are considered ideal materials for surface protective coatings.In this study， a FeCrBSi medium-entropy alloy coating was prepared on the surface of 316L stainless steel via laser cladding technology.The microstructure and tribocorrosion coupling behavior of the cladded layer were analyzed using X-ray diffraction (XRD)， metallographic microscopy and electrochemical corrosion and tribological tester.Results showed that the cladding layer consisted of dual-phase FCC and BCC solid solutions.The cladded zone was primarily composed of dendritic structures， while the bonding zone exhibited planar crystals.The average hardness of the FeCrBSi medium-entropy alloy coating reached 939 HV0.2， approximately 4.4 times that of the 316L stainless steel substrate.As the applied frictional load increased， the coefficient of friction of the coating decreased， with average values ranging from 0.2 to 0.5.The maximum wear volume was 0.052 mm3， indicating a significant improvement in wear resistance compared to the substrate.Electrochemical testing in a 3.5%(mass fraction) NaCl solution demonstrated superior corrosion resistance compared to 316L stainless steel， as indicated by a self-corrosion potential of -0.05 V and a corrosion current density of 1.45×10－7 A/cm2.Under the combined effect of frictional load and externally applied corrosion potential， both the average current density and wear volume increased with increasing potential， while the friction coefficient decreased.A synergistic interaction between corrosion and wear was observed.Notably， corrosion-induced wear contributed over 92.5%to the total material loss， demonstrating its dominant role.